An atypical case of ttp in the emergency department with abdominal pain and seizures - Yigit M.; ÇETİN G.; Turkdogan K. A.; Sogut O.; Soytas R. B. (My University, 2014)
Thrombotic thrombocytopenic purpura (TTP) is a rare autoimmune disease defined by neurological symptoms and deficiencies, fever, renal dysfunction, thrombocytopenia, microangiopathic haemolytic anaemia. Its symptoms are similar to many other diseases. Unless diagnosed and treated appropriately early, TTP can be life threatening with a fatality rate of 90%. TTP must be definitely considered in aetiology of patients presented to emergency department (ED) with seizures and fever and this must take place in differential diagnosis.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (Med); Klinik Tıp; Tıp Genel & Dahili; Clinical Medicine (Med); Clinical Medicine; Medicine General & Internal; Genel Tıp; General Medicine; Abdominal pain; Seizures; Thrombocytopenia; Thrombotic thrombocytopenic purpura